Metal Ions Doped Chitosan Nanoparticles - L.B. Sukhodub (Журнал нано- та електронної фізики)
Microelements in human body which are presented in trace quantities (“trace elements”) play essential role in the regulation of cellular functions, activate or inhibit the enzymatic processes. Modification of bioactive materials for orthopedic implants by inorganic ions to initiate controlled reactions in the tissue surrounding the implant is one of the modern approaches in medical research. The tasks of this work included the obtaining of Chitosan nanoparticles, metal ions Ag +, Cu2 +, Zn2 +, Mg2 +, Fe2 + doped Chitosan nanoparticles, investigation of their antimicrobial properties to the reference microorganisms S. Aureus ATCC 25923, E. Coli ATCC 25922, C. Albicans ATCC 653885 for further use as components in creating composite biomaterials for medical purposes.